PENGARUH POLA ASUH ORANG TUA TERHADAP KENAKALAN REMAJA - Savitri Suryandari (JIPD (Jurnal Inovasi Pendidikan Dasar), 2020)
Juvenile delinquency at this time has occurred almost in all corners of the country, Factors that influence delinquency in adolescents one of his parenting patterns from parents. Forms of juvenile delinquency can be categorized into ordinary delinquency, delinquency that leads to violations and crime or crime and delinquency that is specific. The characteristics that occur in naughty adolescents include differences in intelligence structure, physical and psychological differences as well as personality differences. Parental parenting consists of Authoritarian parenting, Authoritative parenting, permissive parenting and neglect parenting. The results of this study are to determine the effect of parenting parents on juvenile delinquency and how to overcome them.